Subacute pyridostigmine exposure increases heart rate recovery and cardiac parasympathetic tone in rats. (August 2017) - Bharadwaj, Manushree; Pope, Carey; Davis, Michael; Katz, Stuart; Cook, Christian; Maxwell, Lara
Summary: Heart rate recovery (HRR) describes the rapid deceleration of heart rate after strenuous exercise and is an indicator of parasympathetic tone. A reduction in parasympathetic tone occurs in patients with congestive heart failure, resulting in prolonged HRR. Acetylcholinesterase inhibitors, such as pyridostigmine, can enhance parasympathetic tone by increasing cholinergic input to the heart. The objective of this study was to develop a rodent model of HRR to test the hypothesis that subacute pyridostigmine administration decreases cholinesterase activity and accelerates HRR in rats. Ten days after implantation of radiotelemetry transmitters, male Sprague Dawley rats were randomized to control (CTL) or treated (PYR; 0.14 mg/mL pyridostigmine in the drinking water, 29 days) groups. Rats were exercised on a treadmill to record HRR, and blood samples were collected on days 0, 7, 14, and 28 of pyridostigmine administration. Total cholinesterase and acetylcholinesterase (AChE) activity in plasma was decreased by 32%‐43% and 57%‐80%, respectively, in PYR rats on days 7‐28, while plasma butyrylcholinesterase activity did not significantly change. AChE activity in red blood cells was markedly reduced by 64%‐66%. HRR recorded 1 minute after exercise was higher in the PYR group on days 7, 14 and 28, and on day 7 when HRR was estimated at 3 and 5 minutes. Autonomic tone was evaluated pharmacologically using sequential administration of muscarinic (atropine) and adrenergic (propranolol) blockers. Parasympathetic tone was increased in PYR rats as compared with the CTL group. These data support the study hypothesis that subacute pyridostigmine administration enhances HRR by increasing cardiac parasympathetic tone.